2005
DOI: 10.1039/b504728e
|View full text |Cite
|
Sign up to set email alerts
|

The organic composition of diesel particulate matter, diesel fuel and engine oil of a non-road diesel generator

Abstract: Diesel-powered equipment is known to emit significant quantities of fine particulate matter to the atmosphere. Numerous organic compounds can be adsorbed onto the surfaces of these inhalable particles, among which polycyclic aromatic hydrocarbons (PAHs) are considered potential occupational carcinogens. Guidelines have been established by various agencies regarding diesel emissions and various control technologies are under development. The purpose of this study is to identify, quantify and compare the organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(52 citation statements)
references
References 23 publications
5
45
2
Order By: Relevance
“…Liang et al (2005) characterized diesel PM emitted from non-road engines using a dynamometer test and found that n-alkanes accounted for 0.83 % of PM, which is lower than the proportion found in this study. This result could be attributed to the lowsulfur diesel fuel and the different sampling methods they used.…”
Section: Particulate Matter Composition For Individual Excavatorcontrasting
confidence: 43%
See 1 more Smart Citation
“…Liang et al (2005) characterized diesel PM emitted from non-road engines using a dynamometer test and found that n-alkanes accounted for 0.83 % of PM, which is lower than the proportion found in this study. This result could be attributed to the lowsulfur diesel fuel and the different sampling methods they used.…”
Section: Particulate Matter Composition For Individual Excavatorcontrasting
confidence: 43%
“…Fuel quality has a significant effect on PM emissions from vehicles (Cui et al, 2016;Liang et al, 2005;Zhang and Balasubramanian, 2014). Because various fuels are used in excavators and always have poor qualities, all of the corresponding fuels from each of the tested excavators were collected for quality analysis.…”
Section: Chemical Analysis 231 Fuel Quality Analysismentioning
confidence: 99%
“…3), which was predominated by C 1 -naphthanes and C 2 -naphthanes (Bernabei et al, 2003;Saeed and Al-Mutairi, 2004). Although diesel fuel has been commonly used in Antarctica, the composition profiles of PAHs in the lakes were slightly different from the known profiles of diesel fuel, which were evidenced by the predominance of C 2 -naphthanes and C 3 -naphthanes (Dobbins et al, 2006;Liang et al, 2005). This finding suggested that diesel fuel may be partly responsible for PAHs loading to the lakes.…”
Section: Source Diagnostics Of Pahsmentioning
confidence: 69%
“…(Fig. 1), several jet fuel and diesel fuel samples acquired from the literature (Bernabei et al, 2003;Christie et al, 2012;Dobbins et al, 2006;Liang et al, 2005;Rhead and Hardy, 2003;Shumway, 2000), exhaust particulate matter (PM) from combustion of jet fuel (Christie et al, 2012), gas phase emitted from motor vehicle traffic in a Log Angel roadway tunnel (Fraser et al, 1998), water-soluble fraction of aviation fuel (Saeed and Al-Mutairi, 2004), and seawater as obtained by semipermeable membrane device (SPMD) around an oil platform off the Norwegian coast (Harman et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The detailed procedures of DPM extraction and instrumental analysis have been published elsewhere. 33 The extracted solution was concentrated by nitrogen purging to approximately 1 mL for GC/MS analysis.…”
Section: Determinations Of N-alkanes and Pahsmentioning
confidence: 99%